Characterization of Do-It-Yourself (DIY) Ultra Compact ITERA Robotic Telescope (UTOPIA-Scope) Mounting - Barends, Renza Alvionzo; Prastyo, Hendra Agus; Rozzykin, Achmad Zainur; Wahidin, Alka Budi; Wibowo, Ridlo Wahyudi; Yusuf, Aditya Abdilah; Oktaviandra, Adhitya (Indonesian Journal of Aerospace, 2025)
Low-cost and locally fabricated robotic telescope systems are increasingly important for education, amateur astronomy, and basic scientific observation. This paper presents the characterization of the UTOPIA-Scope, a do-it-yourself (DIY) alt-azimuth robotic telescope mount developed using extruded aluminum structures and 3D-printed strain-wave gears. The performance of the mount was evaluated through pointing and tracking tests using an alt-azimuth grid and selected equatorial stars. Image center coordinates were obtained using plate-solving techniques and analyzed with descriptive statistical methods. The results show average pointing errors of 1.600° ± 0.123° in azimuth, 0.415° ± 0.048° in altitude, and 0.451° ± 0.106° in equatorial pointing, corresponding to approximately 96′, 25′, and 27′, respectively. Tracking tests indicate drift rates of 22–36 arcsec per minute, depending on the observed sky region. These results provide a quantitative baseline for the performance of the UTOPIA-Scope mount and serve as a reference for further mechanical and control-system improvements toward future scientific applications.